Theory of Knowledge and Crisis of Paradigms: international relations and international scientific cooperation post-pandemic - Valim, André Luiz Vieira (Cadernos Eletrônicos Direito Internacional sem Fronteiras, 2023)
This article aims to study the concepts, conceptions and approaches on science, theory, paradigm and hypotheses formulated specifically in the works of Thomas Kuhn (Structures of Scientific Revolutions) and Boaventura de Sousa Santos (A discourse on the Sciences; and, The Cruel Pedagogy of the Virus) the latter about the social consequences of a post-pandemic world. Thus, we intend to understand how the theory of knowledge about the differentiation between common sense and scientific knowledge has been the subject of discussions for decades and are even more relevant in a world that has proved fragile and sensitive, globally and generally, in the face of the coronavirus pandemic (Covid-19) in 2020. This public health emergency of international importance that culminated in the infection of millions of people in hundreds of countries, causing thousands of deaths, presented itself as a crisis in knowledge and health practices, international relations and science as knowledge and practices; thus demonstrating the imprescindibility of a world-class diplomatic combination in relation to indiscernible problems and issues that do not respect borders, sovereignties or military or economic powers. The specific objective aims to verify and demonstrate how international relations in the post-pandemic should therefore be directed by desiderates of international scientific cooperation and expansion of knowledge on issues and issues that affect all nations. Just as in the decades of the first half of the 20th century the abolition of war and the search for peace between states were the desideratum of countries, in the 21st century the paradigm of relations between nations should be the search for international scientific cooperation for the life, dignity, security and well-being of subjects of international law and with the valorization of human rights as leading normative elements and also as international norms of universal commitment.